Intraocular lens durability after a mean of 10.9 years' implantation in humans - Shoji, E. (1997)
AIMS/BACKGROUND—To clarify whether intraocular lens (IOL) implantation in the human eye affects the durability of polymethylmethacrylate over an average period of 10.9( )years. METHODS—Shearing stress and extent of damage following neodymium (Nd):YAG laser application to 18 study and 12 control optics were examined. RESULTS—No significant difference was found between the study and the control IOLs in shearing stress and extent of damage following Nd:YAG. CONCLUSION—An average 10.9 years' implantation in humans does not affect either the shearing stress or extent of damage following Nd:YAG shots of polymethylmethacrylate.